2022
DOI: 10.1039/d1fo03486c
|View full text |Cite
|
Sign up to set email alerts
|

Glucopyranose from Pleurotus geesteranus prevent alcoholic liver diseases by regulating Nrf2/HO-1-TLR4/NF-κB signalling pathways and gut microbiota

Abstract: This study investigated the effects of PGPs, a glucopyranose isolated from the mycelium of Pleurotus geesteranus and characterized with the main chain of →4)-α-D-Glcp-(1→, on the prevention against alcohol liver...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Accumulating evidences suggest that excessive alcohol intake may cause the disorders of intestinal microbial homeostasis and the permeability of intestinal barrier, resulting in the proliferation of harmful bacteria in the intestinal tract, the absorption of harmful metabolites, and the damage of liver metabolism function ( Tian et al, 2020 ). Previous study had shown that the intestines of alcoholics are characterized by lower abundance of Eisenbergiella and Akkermansia , but higher proportion of Odoribacter , Parasutterella and Psychrobacter ( Sang et al, 2021 ; Song et al, 2021 ; Cao et al, 2021 ). According to the previous report, Bifidobacterium and Akkermansia could significantly improve the intestinal barrier function and reduce the damage caused by alcohol metabolites (acetaldehyde and free radicals) to the liver in mice with excessive alcohol intake ( Bajaj, 2019 ).…”
Section: Introductionmentioning
confidence: 97%
“…Accumulating evidences suggest that excessive alcohol intake may cause the disorders of intestinal microbial homeostasis and the permeability of intestinal barrier, resulting in the proliferation of harmful bacteria in the intestinal tract, the absorption of harmful metabolites, and the damage of liver metabolism function ( Tian et al, 2020 ). Previous study had shown that the intestines of alcoholics are characterized by lower abundance of Eisenbergiella and Akkermansia , but higher proportion of Odoribacter , Parasutterella and Psychrobacter ( Sang et al, 2021 ; Song et al, 2021 ; Cao et al, 2021 ). According to the previous report, Bifidobacterium and Akkermansia could significantly improve the intestinal barrier function and reduce the damage caused by alcohol metabolites (acetaldehyde and free radicals) to the liver in mice with excessive alcohol intake ( Bajaj, 2019 ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, it was reported that alcohol might increase intestinal permeability, which could lead to increased levels of pathogens such as lipopolysaccharide (LPS) (Hong et al, 2019; Szabo & Bala, 2010). Then, LPS is transferred to the liver via the portal circulation, where it binds to TLR4, a major component of the LPS recognition receptor complex, releasing ROS and large amounts of proinflammatory cytokines (Song et al, 2022). A previous study has shown that nucleic acids such as RNA facilitated the development of the mouse intestine and the proliferation of intestinal epithelial cells (Xie et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…DOP, EPP, PFP-1, PNP80b-2, and TASP could ameliorate alcohol-induced hepatic oxidative stress via promoting the transcription of antioxidant genes mediated by nuclear factor E2-related factor 2 (Nrf2) [ 50 , 51 , 52 , 54 , 56 ]. Polysaccharides from Pleurotus geesteranus mycelium, LBP, DOP, and EPP could ameliorate alcohol-induced hepatic inflammatory damage by inhibiting nuclear factor kappa-B (NF-κB) signaling pathways [ 50 , 56 , 60 ] or by reducing-thioredoxin interacting protein (TXNIP)-induced NLRP3 inflammasome formation [ 55 , 56 ]. Besides, EPP, CPS, PFP-1, MPCC, APCC, Pleurotus geesteranus mycelium polysaccharide, GP, TASP, and MP could reverse ethanol-induced lipid disorder, i.e., decreasing serum triglycerides, total cholesterol, and low-density lipoprotein cholesterol (LDL-C) and increasing serum high-density lipoprotein cholesterol (HDL-C) [ 46 , 48 , 50 , 51 , 53 , 54 , 55 , 57 , 58 , 59 ].…”
Section: Polysaccharides In Different Liver Diseasesmentioning
confidence: 99%